2011
DOI: 10.31047/1668.298x.v28.n1.2777
|View full text |Cite
|
Sign up to set email alerts
|

Eficiencia en el uso de la radiación en papa estimada a partir de la cobertura del follaje

Abstract: La eficiencia en el uso de la radiación (EUR) de un cultivo es la relación entre la materia seca producida y la radiación fotosintéticamente activa interceptada(RFAI) durante su ciclo. La fracción de radiación fotosintéticamente activa interceptada (fRFAI) puede determinarse mediante el método tradicional de Beer, a partir del índice de área foliar (iaf), o empleando la cobertura del suelo (f), como medida subrogante de fRFAI. Cuando el iaf en papa supera 3, el valor de fRFAI cambia muy poco, haciendo muy difí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(40 reference statements)
1
2
0
4
Order By: Relevance
“…The RUE values were within the wide range reported in the literature for Solanum tuberosum , based on PAR under field conditions (1.07–3.7 g MJ ) [ 53 , 55 , 56 ]. According to Quiroz et al [ 10 ], potatoes are able to show plasticity in RUE responses with an increment (5.4 g MJ , the highest value reported in the literature) under cloudy environments.…”
Section: Discussionsupporting
confidence: 80%
“…The RUE values were within the wide range reported in the literature for Solanum tuberosum , based on PAR under field conditions (1.07–3.7 g MJ ) [ 53 , 55 , 56 ]. According to Quiroz et al [ 10 ], potatoes are able to show plasticity in RUE responses with an increment (5.4 g MJ , the highest value reported in the literature) under cloudy environments.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have shown the highest light absorption efficiency values at the LAI value of 3, which corresponded to maximum ground cover. If potato LAI exceeds 3, the intercepted photosynthetically active radiation value changes very little [39,40]. According to Howlader and Hoque [41], irrespective of potato cultivars, LAI increased progressively over time, reaching a peak at 60 days after planting and thereafter declining.…”
Section: Discussionmentioning
confidence: 99%
“…De la Casa et al . (2011), who determined RUE for a potato crop and analysed the values of LAI and GCC, found that maximum canopy cover (98%) occurred at an LAI of 3–4 m 2 /m 2 . In addition, De la Casa et al .…”
Section: Discussionmentioning
confidence: 99%